Introduction to environmental engineering - Kahl, Alandra (Environmental engineering collection, 2016)
Key topics in environmental engineering are discussed in sufficient detail as to provide a concise and useful overview for the graduate or professional student. Subjects approached herein include water and wastewater treatment systems, hazardous materials, and alternative energy. The intent of this volume is to provide a repository of general information for consultation and reference of the user.